21st century STEM education: An increase in mathematical critical thinking skills and gender through technological integration - Suherman Suherman; Revani Husain Setiawan; Herdian Herdian; Bambang Sri Anggoro (Journal of Advanced Sciences and Mathematics Education, 2021)
STEM learning is a process of improving one's mathematical critical thinking skills in the twenty-first century. The study aimed to compare the mathematical skills of critical thinking between genders through STEM learning. The researchers employed the quasi-experiment design with 2 x 2 factorial designs and a simple random sampling technique. The research data were collected using tests to assess students' mathematical critical thinking skills. The normality, homogeneity, and hypothesis tests analysis were performed using two-way ANOVA. The research findings are as follows: (1) there were differences between STEM and conventional learning in mathematical critical thinking skills. STEM learning through technological integration is more effective than conventional learning; (2) there was a difference in the mathematical critical thinking skills results between male and female students, with female students having a higher ability to use critical thinking skills. It is expected that STEM learning can be used as a learning solution in the twenty-first century.